China-Nigeria Relations and its Impact on Nigeria’s Democratic Stability in the 4th Republic- 2015-2025 - Bedekenana, Etegbiku Glory; Etemike, Lazarus (Indonesian Journal of Political Studies, 2025)
China–Nigeria relations have expanded significantly between 2015 and 2025, with important implications for Nigeria’s democratic stability in the Fourth Republic. This study examines the political, economic, and governance dimensions of the partnership, focusing on how Chinese investments and strategic engagements have shaped Nigeria’s democratic processes. China’s involvement is most visible in infrastructure, trade, digital technology, and security cooperation, presenting an alternative to Western aid that typically carries political conditions. While these engagements help address infrastructure deficits and stimulate economic growth, they also raise concerns about governance transparency, accountability, and civil liberties. Risks include opaque loan agreements, elite capture of Chinese-funded projects, and the spread of digital surveillance technologies that may reinforce authoritarian practices. The research further shows how Nigerian elites exploit Chinese partnerships as political capital, showcasing infrastructure projects to consolidate legitimacy during elections. Overall, the findings suggest that China–Nigeria relations create both opportunities for economic transformation and challenges for democratic governance, with Nigeria’s long-term stability hinging on balancing cooperation benefits with institutional safeguards.